Study of the cognitive functions of children displaced from the South-East of Ukraine (zone of the antiterrorist operation) - Lisukha Любов (Psychosomatic Medicine and General Practice, 2018)
This is a conference abstract from the "Psychosomatic Medicine Of The XXI Century: Realities And Perspectives" Congress. It is dedicated to the study of cognitive functions of children who have been moved from the southeast of Ukraine.